Choosing a method for poverty mapping - Davis, Benjamin (FAO, 2003)
Presents and compares a large selection of poverty and food-security mapping methodologies in use. The choice of a poverty-mapping methodology depends on a number of logical and legitimate considerations, such as the objectives of the poverty mapping exercise, philosophical views on poverty, limits on data and analytical capacity, and cost
33
Keywords: Poverty; Income distribution; Economics